The effect of the small-molecule luteinising hormone receptor agonist, LHR-Chap, on receptor trafficking and G protein-independent signalling. - Newton, Claire (University of Pretoria, 2022)
Dissertation (MSc (Human Physiology))--University of Pretoria, 2022.